2015
DOI: 10.1021/acsami.5b04043
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Thin Films of α-Fe2O3 via Atomic Layer Deposition Using Iron Bisamidinate and Water under Mild Growth Conditions

Abstract: Atomic layer deposition (ALD) has been shown to be an excellent method for depositing thin films of iron oxide. With limited iron precursors available, the methods widely used require harsh conditions such as high temperatures and/or the use of oxidants such as ozone or peroxide. This letter aims to show that bis(N,N'-di-t-butylacetamidinato) iron(II) (iron bisamidinate or FeAMD) is an ideal ALD precursor because of its reactivity with water and relative volatility. Using in situ QCM analysis, we show outstand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 28 publications
3
12
1
Order By: Relevance
“…The constant growth rate of 0.47 Å per cycle was confirmed again, leading to 90 nm thick films by applying 2000 cycles. The growth rates obtained are comparable to the results of Avila et al when using iron bisamidinate and water as precursors and are among the highest observed for ALD grown iron oxide so far . As expected for surface controlled ALD‐type growth, the surface roughness of the films was low and did not vary as a function of the deposition temperature inside the ALD window.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The constant growth rate of 0.47 Å per cycle was confirmed again, leading to 90 nm thick films by applying 2000 cycles. The growth rates obtained are comparable to the results of Avila et al when using iron bisamidinate and water as precursors and are among the highest observed for ALD grown iron oxide so far . As expected for surface controlled ALD‐type growth, the surface roughness of the films was low and did not vary as a function of the deposition temperature inside the ALD window.…”
Section: Resultssupporting
confidence: 85%
“…After annealing (500 °C) at ambient atmosphere and pressure for 1 h, however, the amorphous deposits were transformed to crystalline hematite ( Figure ). The amorphous appearance of the ALD grown iron oxides originates from the low deposition temperature and the low layer thickness, which hinders the crystallization as already reported by Avila et al previously . All deposits have been characterized in terms of composition by Rutherford backscattering (RBS) and nuclear reaction analysis (NRA) (Figure S9 and Table S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…To address these issues and to meet such requirements, thermal ALD and PEALD can be used. For instance, iron oxide films can be deposited at temperatures ranging from 150 °C to 500 °C by thermal ALD [36][37][38][70][71][72], and by PEALD [73]. Cobalt and nickel films can be deposited at temperatures ranging from 125 °C to 350 °C by thermal ALD [41,[74][75][76][77][78], and PEALD [39,[79][80][81].…”
Section: Cvd Of Fe Co and Nimentioning
confidence: 99%
“…Due to its widespread application potential, the synthesis of well-defined ferromagnetic IONP’s has emerged as a widely investigated research niche. Currently, most synthesis protocols rely heavily on chemical methods including co-precipitation [ 11 ], thermal decomposition [ 12 ], atomic layer deposition, [ 13 ] and sol–gel processes [ 14 ], or physical protocols such as ball milling [ 15 ], electron beam evaporation [ 16 ], radio frequency (RF) sputtering [ 17 ] or sonochemical synthesis [ 18 ]. Although these methods produce predictable outcomes, they require rigorous adherence to stringent protocols and entail a high cost and energy investment.…”
Section: Introductionmentioning
confidence: 99%